Sojourners’ Dystopia in P. D. James’s The Children of Men - Seda Coşar Çelik (Journal of Literature and Humanities, 2025)
This article intends to explore different portrayals of sojourners in P.D. James’s 1992 novel, The Children of Men, and Alfonso Cuarón’s 2006 film adaptation with the same title. Through their divergent perspectives on life and social anxieties within a dystopian world, these works offer unique insights into the fear of depopulation. The issue of mass infertility and the plight of people living under a totalitarian government stands at the center of each narrative. Also, in both works, the immigrants are brought to the UK to do various undesirable and laborious work, and they do not have any rights and civil existence in society. The immigrant issue occupies a place in both the novel and the film with varying degrees of importance. Thus, the article aims to explore how the portrayal of immigrants and their agency in each narrative change. Concisely, while the novel centers on mass infertility and rapid population decline, the film amplifies the plight and role of immigrants in a depopulating world. The article argues that this shift in focus may reflect the intensified anxieties surrounding the escalating human mobility on a global scale.